2023
DOI: 10.1038/s41598-023-35664-w
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of action observation to drag the trainees' motor pattern toward the observed model

Maria Chiara Bazzini,
Arturo Nuara,
Giulio Branchini
et al.

Abstract: Action Observation Training (AOT) promotes the acquisition of motor abilities. However, while the cortical modulations associated with the AOT efficacy are well known, few studies investigated the AOT peripheral neural correlates and whether their dynamics move towards the observed model during the training. We administered seventy-two participants (randomized into AOT and Control groups) with training for learning to grasp marbles with chopsticks. Execution practice was preceded by an observation session, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Indeed, while control training did not induce any significant modulation over time, AOT was able to polarize the trainee’s expressive pattern toward those of the observed model. Such a “dragging effect” is consistent with recent experiments showing that the improvement of the motor performance induced by AOT is linked to the increase of similarity of the observer’s motor pattern toward the model ( 24 ). The observation of hand-keys interaction, coupled with prominent acoustical information, may have sculpted a more comprehensive motor representation, in turn promoting a more similar motor performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, while control training did not induce any significant modulation over time, AOT was able to polarize the trainee’s expressive pattern toward those of the observed model. Such a “dragging effect” is consistent with recent experiments showing that the improvement of the motor performance induced by AOT is linked to the increase of similarity of the observer’s motor pattern toward the model ( 24 ). The observation of hand-keys interaction, coupled with prominent acoustical information, may have sculpted a more comprehensive motor representation, in turn promoting a more similar motor performance.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, a growing body of research has pointed out that motor training based on action observation boosts the improvement of motor skills in a wide range of human activities ( 10 , 23 , 24 ). In the present study, we investigated whether the same potentiality can be applied also to the music realm and, if this is the case, which aspects of musical performance were mostly impacted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to control the duration of the recordings and the number of movements and repetitions when designing protocols. In the case of AO, protocols and studies that have been carried out using EMG have shown that muscle activation occurs, and, after training, changes in the contraction of the muscles were studied [ 37 , 38 ]. However, these studies have not been conducted in the therapeutic field, so demonstrating that protocols of this type are effective may open doors in neurorehabilitation.…”
Section: Expected Resultsmentioning
confidence: 99%